Comparative transcriptome profiling of Kappaphycus alvarezii (Rhodophyta, Gigartinales) in response to two extreme temperature treatments: an RNA-seq-based resource for photosynthesis research. Issue 2 (3rd April 2019) - Li, Qianqian; Zhang, Litao; Pang, Tong; Liu, Jianguo
ABSTRACT: Kappaphycus alvarezii provides an important raw material for the extraction of κ-carrageenan. Comparative transcriptome analysis of K. alvarezii after 24 h extreme temperature treatments (17°C and 34°C) was performed to uncover the molecular mechanisms controlling temperature-related photosynthesis regulation. Optimum temperature (28°C) was employed as the control. After de novo assembly of these three transcriptome samples and searching the assembled transcripts by BLAST against the NCBI nr databases, 11, 537 top-hit transcripts were assigned as unigenes. Through comparisons, 302 significantly differentially expressed genes were identified. Twenty-three of the differentially expressed unigenes encoded photosystem antenna protein subunits and a further 25 were associated more broadly with photosynthesis functions. Compared to the light-harvesting complex (LHC) protein, the expression of phycobiliproteins (PBPs) was stable after extreme low and high temperature (ELT/EHT) treatments. Both ELT and EHT were found to inhibit the expression of subunits of photosystem II (PsbA, PsbC, Psb27, PsbW, PsbS), photosystem I (PsaF, PsaG, PsaK) and photosynthetic electron transport (PetE). These results were confirmed through targeted analysis of the mRNA and protein abundance of individual proteins, and were congruent with the results of chlorophyll a fluorescence (OJIP) measurements performed with temperature-stressed lines. In conclusion, similarities and differences in the behaviours of photosynthesis-related genes were summarized to provide opportunities for understanding the responses of K. alvarezii after extreme temperature treatments.